(untitled) (Global Journals of Research in Engineering, 2023)
The main objective of the research being conducted is not only to achieve the required soil engineering properties by mixing this product but also to consider the effect of this product of soils stabilization on fine particles contained in lateritic and typically clayey soils This research work presents the efficiency of calcium Silicate as an additive in improving the engineering characteristics of laterite aggregate soil and clayey soils Investigations will be done to evaluate the effectiveness of this soil stabilizer which involved the use of calcium Silicate CaSiO3 formula fixed by Ndiaye et al 2022 As a chemical additive the percentage of the binder will be respectively 4 and 6 These two types of soils are expected to be stabilized and their effectiveness will be observed from the expected results only in terms of strength and consolidation by constant rate of strain parameters like recompression index Cr and compression index Cc The results of the tests conducted in Oregon State University on laterite aggregate soil showed that the compression strength UCS gives a value of 1 4 MPa for SH85 treated samples against 1 5 MPa for Portland cement ones but with a minimum of strain under alternating temperature conditions However this evolution is even more important on clay samples reaching 1 01 MPa of stress for dry black clay against 0 44 MPa for the dried black clay as peaks The alternating wet and dried conditions were crucial as well as the specimens sizes